The colonial divide in Peruvian narrative : social conflict and transculturation - Kokotovic, Misha (Brighton [England] ; Portland, Or. : Sussex Academic Press, 2005)
"Peru is a nation built on the still extant colonial divide between indigenous peoples and the descendants of their Spanish conquerors. The Colonial Divide in Peruvian Narrative explores how Arguedas, Vargas Llosa, and others confronted challenges of language, style, and narrative form in their attempt to write across their nation's cultural divisions. It examines how modernization affected the relationship between Peru's white elite and its indigenous majority, how historical change stimulated the emergence of new narrative techniques, and how these in turn made possible an understanding of the historical contexts in which they arose."
"Though Peru is its principal focus, the text engages with current studies of modernity at the postcolonial margins of the Western world by contributing to an understanding of the class and ethnic conflicts generated by rapid modernization in culturally heterogeneous nations."--Jacket.
Modernity from the margins : narrative form and indigenous agency in Broad and alien is the world and Yawar fiesta -- From development theory to pachakutiy : José María Arguedas's anthropology and fiction in the 1950s -- Between feudalism and imperialism : indigenous culture and class struggle in All the worlds and Drums for Rancas -- The criollo city transformed : Andean migration in urban narrative -- Mario Vargas Llosa writes of(f) the native : cultural heterogeneity and neoliberal modernity.
Includes bibliographical references (pages 257-271) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Peruvian fiction -- 20th century -- History and criticism; Social conflict in literature; Group identity in literature; Literature and society -- Peru; Roman péruvien -- 20e siècle -- Histoire et critique; Conflits sociaux dans la littérature.; Identité collective dans la littérature.; Littérature et société -- Pérou.; 18.33 Spanish-American literature; Novela peruana -- S.XX -- Historia y crítica; Conflictos sociales -- En la literatura; Group identity in literature; Literature and society; Peruvian fiction; Social conflict in literature; Peru; Literatur; Sozialer Konflikt; Peru; Literature; Acculturation; Social conflicts; Spanish; Peru; 1900-1999; 1900-2000.; Geschichte 1900-2000; Criticism, interpretation, etc